2013
DOI: 10.5897/2013.5696
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of phosphate by the Bacillus under salt stress and in the presence of osmoprotectant compounds

Abstract: The Bacillus by their intrinsic properties have several mechanisms of procuring beneficial effects to plants. They are among the most successful bacterial communities in the solubilization of phosphates. Ten Bacillus strains were isolated from the rhizosphere of wheat from three areas in arid and semi-arid regions in Algeria. These strains were tested for their ability to solubilize phosphates on liquid and solid media: LB (Luria-Bertani), NBRIP (National Botanical Research Institute Phosphate) and PVK (Pikovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To assess the strains' ability to dissolve inorganic phosphate, 5 mm agar plugs of each actinomycete strains (collected from cultivated plates of ISP2 media kept at 30 • C for 7 days) were placed in plates with three different media containing Ca 3 (PO 4 ) 2 as the only source of phosphate: NBRIP (National Botanical Research Institute's Growth Medium) [26], PVK (Pikovskaya) [27], and LB (Luria Bertani) modified by glucose addition. The solubilization ability was estimated by measuring the transparent area formed around the colony after 7 days of incubation at 30 • C. The diameter of the solubilization halo for each isolate was determined by subtracting colony diameter from the total one (diameter of the halo -diameter of the colony) [28].…”
Section: Phosphate Solubilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the strains' ability to dissolve inorganic phosphate, 5 mm agar plugs of each actinomycete strains (collected from cultivated plates of ISP2 media kept at 30 • C for 7 days) were placed in plates with three different media containing Ca 3 (PO 4 ) 2 as the only source of phosphate: NBRIP (National Botanical Research Institute's Growth Medium) [26], PVK (Pikovskaya) [27], and LB (Luria Bertani) modified by glucose addition. The solubilization ability was estimated by measuring the transparent area formed around the colony after 7 days of incubation at 30 • C. The diameter of the solubilization halo for each isolate was determined by subtracting colony diameter from the total one (diameter of the halo -diameter of the colony) [28].…”
Section: Phosphate Solubilizationmentioning
confidence: 99%
“…Spore suspension of each strain (100 µL) was inoculated in 10 mL of liquid PVK medium and incubated at 30 • C for 7 days in a rotary shaker at 150 rpm. After incubation, the cultures were centrifuged at 3000 rpm for 20 min [28], and the solubilized phosphorus was quantified in the supernatant by the colorimetric method of Olsen and Sommers [29].…”
Section: Phosphate Solubilizationmentioning
confidence: 99%
“…These results are in accordance with the results of Nautiyal et al [ 39 ], who classified the liquid NBRIP medium as the best medium for testing the phosphate solubilization. Cherif et al [ 40 ] and Chibani et al [ 41 ] also reported that NBRIP is the preferred liquid medium for phosphate solubilization by the majority of rhizobacteria.…”
Section: Resultsmentioning
confidence: 99%